Concepts,issues,and applications of fog computing - Weijia JIA; Xiaojie ZHOU (Tongxin xuebao, 2018)
Firstly,the previous work of fog computing was systematically analyzed and summarized.The background of fog computing and the comparison with cloud computing were introduced.Besides,based on the comparison with other computing style,the advantages and characteristics of fog computing were explained.In addition,the architecture of fog computing was described.Moreover,network management and resource scheduling of fog computing were discussed,where the related previous work were summarized and analyzed.At last,the applications of fog computing were described.Taking the intelligent driving and industrial Internet of things applications as examples,the key research issues of fog computing were proposed.